CAUSES AND RELEVANCE OF CHRONIC HEART FAILURE - Alibek Askarovich Khudaynazarov,; Zafar Abdunaemovich Sharapov, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Heart failure is sometimes a complication of other organ diseases, including those affecting or damaging the heart muscle. Heart failure is a syndrome caused by decompensated myocardial dysfunction. It is characterized by an increase in interstitial fluid volume and decreased organ and tissue perfusion. The pathophysiological basis of this syndrome is the inability of the heart to meet metabolic demands. It often develops as a complication of previous or ongoing illnesses that damage the heart muscle or place additional strain on it. In addition to the most common causes, there are other causes of heart failure. These include abnormal pressure in the heart's blood vessels, coronary artery disease, heart valve disease, heart muscle disease, and arrhythmia. The most common cause of chronic heart failure is coronary artery disease. Heart failure can develop at any age, but is most common in older adults.